«Живешь только дважды»: Временные особенности Закарпатской области на примере венгерских элементов - Шилов, Володимир (SlavVaria, 2023)
“You only live twice”: Time features of the Transcarpathian region on the example of Hungarian elements. This work was done as part of the analysis of the linguistic landscape of the Transcarpathian region in Ukraine. The local population can use two time zones at the same time – Eastern European (UTC +2, the only official time in Ukraine) and Central European (UTC +1, the official time in some countries neighboring Transcarpathia, such as Hungary, Slovakia and Poland). Most often, the Central European zone (UTC +1) appears on the Hungarian street inscriptions in Transcarpathia. Therefore, it makes sense to conduct a diachronic study of the use of these elements separately from other languages (Ukrainian, Russian, Slovak, etc.).